Same but different: Larval development and gall-inducing process of a non-pollinating fig wasp compared to that of pollinating fig-wasp - Jansen González, Sergio (2014)
The receptacles of fig trees (Ficus spp.) can harbor a highly diversified and complex community of chalcid wasps. Functional groups of fig wasps (e.g. gallers, cleptoparasites and parasitoids) oviposit into the fig at different developmental stages, reflecting different feeding regimes for these insect larvae. There are few direct data available on larval feeding regimes and access to resources. We studied the gall induction and larval feeding strategy of an Idarnes (group flavicollis) species, a non-pollinating fig wasp (NPFW) associated to Ficus citrifolia P. Miller in Brazil. This Idarnes species shares with the pollinator characteristics such as time of oviposition, ovipositor insertion through flower and location of the egg inside plant ovaries. Nevertheless, we show that the gall induction differs considerably from that of the pollinating species. This Idarnes species relies on the induction of nucellus cell proliferation for gall formation and as the main larval resource. This strategy enables it to develop in both pollinated and unpollinated figs. The large differences between this NPFW and other fig wasps in how ovules are galled suggest that there are different ways to be a galler. A functional analysis of NPFW community structure may require descriptions of the histological processes associated with larval development.